2016
DOI: 10.14687/ijhs.v13i1.3712
|View full text |Cite
|
Sign up to set email alerts
|

Female murderers: Examination of the relationship between childhood traumatic experiences and anger expression

Abstract: Adverse childhood period and abuse experiences may lead to some problems later in life. One of these problems is aggressive behavior, which is thought to be a reflection of the child's increasing anger (Page, 2004;Olive, 2007). Based on the fact that negative childhood experiences can lead to aggressive emotions, investigating the relationship between traumatic childhood experiences and female convicts' aggression expression styles was considered important. Sample of the research consists of 77 females who are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
1
0
2
Order By: Relevance
“…[7]. In consequence of a recent study, carried out on 77 female samples in the penitentiary institution with respect to the relationship between early childhood trauma and anger behaviour, Akduman et al have suggested that those who have experienced trauma histories in the childhood have higher anger scales [38]. Aksu et al have found during their thesis study that there is a nearly significant linear relationship between the fearful attachment scores and state anger levels with respect to those who have penal record due to the violent crimes [39].…”
Section: Discussionmentioning
confidence: 99%
“…[7]. In consequence of a recent study, carried out on 77 female samples in the penitentiary institution with respect to the relationship between early childhood trauma and anger behaviour, Akduman et al have suggested that those who have experienced trauma histories in the childhood have higher anger scales [38]. Aksu et al have found during their thesis study that there is a nearly significant linear relationship between the fearful attachment scores and state anger levels with respect to those who have penal record due to the violent crimes [39].…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Burton ve ark.nın, erkek mahkûmlar üzerinde yürüttükleri araştırmada, kişisel öykülerinde genellikle travma öyküsü ve çocukluklarında kronik bir biçimde şiddet mağduru oldukları ortaya çık-mıştır. 26 Browne ve ark.nın, kadın mahkûmlar üzerinde yürüttükleri bir çalışmada, kadınların %70'inin çocukluklarında ebeveyn ya da bakıcıla-rından yoğun fiziksel şiddet gördükleri bulgusuna ulaşılmıştır.…”
Section: Discussionunclassified
“…27 Akduman ve ark.nın, kadın mahkûmlar üzerinde yaptıkları araştırmada, en sık rastlanan travma kombinasyonun duygusal ve fiziksel istismar kaynaklı olduğu gösterilmiştir. 23 Genç eriş-kin suçlularda çocukluk çağı travmaları yaşantısı-nın araştırıldığı bir çalışmada, travma yaşantısı olan kimselerin büyük ölçüde şiddet suçuna karıştıkları belirtilmektedir. 28 Erken dönemde yaşantılanan istismar türleri ve ihmalin insanlarda dürtü kontrol ve irade problemlerine, impulsif davranışlara ve şiddet içeren suç davranışlarına yol açtığı belirtilmektedir.…”
Section: Discussionunclassified